Analisis Transformasi Gender Pada Tokoh Utama Dalam Film Imperfect Sutradara Ernest Prakarsa. - Putri Aulia; Dani Manesah; Suryanto Suryanto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Gender transformation is an effort to achieve liberation from all forms of oppression, whether structural, personal, class, skin color or international economic. The transformation discussed by the author is gender transformation which is seen based on the appearance of the female main character in the imperfect film which is caused by the work environment, family, and so on, causing the female main character to undergo a gender transformation in appearance. This research aims to ensure that development benefits and resources are directed effectively and fairly to men and women. The method used by the author in this research is a quantitative method. Quantitative method is a research method that uses a lot of numbers. Starting from the data collection process to its interpretation. Meanwhile, the research method is an in-depth and careful study of all the facts.